Reputation and Image from the Perspective of Management Sociology - M. V. Shutova (Дискурс)
Introduction. The digital world is reshaping established realities by enabling social entities to manifest in the online world. Within this evolving framework, reputation increasingly detaches from the individual being assessed, influencing both the dynamics of social interactions and the norms that develop through these exchanges. Concurrently, an individual’s virtual identity has gained prominence, often rivaling the importance of their real-world image. As research interest in concepts of image and reputation grows, the tendency to use these terms interchangeably becomes notable. This convergence highlights the need to clarify and differentiate the meanings of these abstractions under examination.Methodology and sources. This study employs sociological, socio-psychological, linguistic, and interdisciplinary methodologies, drawing on specialized literature, scientific research, and online resources. These sources facilitate an examination of the concepts of image and reputation within the digital society, analyzed through the lens of management sociology.Results and discussion. The analysis of the concept of “image” reveals its intrinsic connection to visual perception and its role as a purposefully constructed and relatively stable phenomenon, based on stereotypes of mass consciousness. Image, as an artificially created symbolic construct, is directed at a specific audience, aiming to guide the perception of that audience in a predetermined manner. Its function is to distinctly define and differentiate an object, while simultaneously shaping audience expectations. In contrast, reputation is not entirely within the subject’s control and cannot be deliberately crafted. It emerges organically from the exchange of opinions and public discourse, serving primarily as an evaluation based on comparing expectations and the outcomes of interactions with individuals or organizations.Conclusion. A sociological examination of the concepts of image and reputation has uncovered intersections across multidisciplinary research and highlighted the distinct sociological dimensions of each. An image, in essence, functions as a simulacrum crafted by the subject to position its object as desirable and engaging for the public. In contrast, reputation emerges as a verbalized evaluation shaped through social interaction within a pragmatic context, acting in the digital society as a tool for modulating control. The image functions as an “entry point”, drawing attention from audiences unfamiliar with its subject. Within a culturally and pragmatically relevant context, image and reputation can synergize effectively to advance the agent's interests. However, conflicts between symbols that image conveys, the expectations it constructs, and the experiences informing reputation may undermine the latter.